A Construction of Summary Writing Efficiency Test of Thai subject for Senior high School Student under The Nong Khai Secondary Education Service Area Office: A Construction of Summary Writing Efficiency Test of Thai subject for Senior high School Student under The Nong Khai Secondary Education Service Area Office - Siriruttanaseesakun, Pachara; Surat, Maneeya (RATANABUTH JOURNAL, 2023)
The objectives of this research were 1) to create a writing competency assessment form for summarizing Thai subjects. For high school students Under the Office of Nong Khai Secondary Education Service Area 2) to study the quality of the Thai language summaries writing ability test 3) to create a manual for the use of the Thai language summaries writing ability test, semester 2, academic year 2022, amount 547 people. The tools used in this research were The Thai Language Conclusion Writing Competence Test consists of 32 questions aimed at measuring the ability to write summaries that include summarizing elements, namely main themes and key points. support message and further explanation It is a situational test, multiple choice, 5 multiple choices, 30 items and 2 subjective items. Statistics for data analysis in this research is to analyze the Index of Concordance (IOC) analysis of difficulty. Analyze the discriminant power value of the item-by-item measurements by using the Item Total Correlation formula to analyze the sentiment by using the method of Kuder-Richardson (KR-20) and Structural Validity Analysis by confirmatory factor analysis (CFA). The results showed that Thai language proficiency test form This is a situational exam suitable for senior high school students. The quality test can be used to measure the ability to write Thai language summaries. for senior high school students effectively .The result of the measurement quality check found that 1) Content validity (IOC) ranged from 0.80 – 1.00 2) Difficulty value ranged from 0.33 – 0.80 3) Classification power ranged from 0.40 – 0.764) Measurement design Structurally accurate which is consistent with empirical data with chi-square ( ) = 332.96 (p = 0.139), df = 306, RMR = 0.031, RMSEA = 0.016, GFI = 0.94 and AGFI = 0.91, and the reliability of the whole paper = 0.86. There was a content validity index of the manual for the ability to measure the ability to write summaries equal to 0.80.